Korupsi Siemens Aktiengesellschaft dalam United Nations-Oil For Food Programme (Un-Offp) di Irak - Sheiffi Puspapertiwi (Global South Review, 2014)
Corruption, as a nontraditional form of crime, occurred when power is abused to gain certain favours for individuals or parties at the expense of the rest. Siemens Aktiengesellscahft (Siemens AG) bribery case is the biggest company corruption revealed in history, in which the company had been convicted guilty for giving bribes to governments in many countries, from developing to developed countries. In Iraq, Siemens AG was proved guilty for giving bribes to Saddam Hussein regime during its involvement in United Nation Oil for Food Programme (UN-OFFP) in 2000-2002. This research is conducted to understand causing factors of such action by employing qualitative data for further analysis. Research finding shows that corruption in UN-OFFP involving three institutions: Siemens AS, Saddam Hussein regime, and UN, was occurred due to pragmatism in pursuing economic motive which encouraged by accommodative culture and enabled by weak law enforcement.